Biological Treatment of Pulp and Paper Industry Effluent by White Rot Fungi Schizophyllum commune and Lenzites eximia - Selvam, K. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT White rot fungi, Schizophyllum commune and Lenzites eximia were collected from the Western Ghats region of Tamil Nadu, India from the living tree of Tamarindus indica and burnt tree respectively. The fungi were isolated using 2% malt extract agar medium and the fungal growth were sub cultured and incubated for 6 day at 370C and maintained on Malt agar slants. Then, the spores were harvested without disturbing the mycelial growth using a camel hairbrush and filter sterilized. The spore concentration was adjusted to 105spores/ml and used as inoculums to treat pulp and paper industry effluents on a laboratory and pilot scales. In laboratory scale a maximum decolourization of 73.9% and 69.5% was achieved by Schizophyllum commune and Lenzites eximia on 6th day respectively. Inorganic chloride at a concentration of 539 mg/l and 534mg/l was liberated by Schizophyllum commune and Lenzites eximia respectively on 6th day of treatment. The chemical oxygen demand (COD) was reduced to 3996mg/l (67.0%) by Schizophyllum commune and 4317mg/l (65.0%) by Lenzites eximia. In Pilot scale, a maximum decolorization of 62.3% was obtained on 6th day of incubation by Schizophyllum commune and 56.20% by Lenzites eximia on 6th day. Inorganic chloride at a concentration of 477 mg/l and 469 mg/l was liberated by Schizophyllum commune and Lenzites eximia respectively on 6th day. The chemical oxygen demand (COD) was reduced to 4798mg/l (61.5%) by Schizophyllum commune and 5196mg/l (56.6%) by Lenzites eximia on 6th day treatment. These results revealed that Schizophyllum commune proved to be more efficient for the treatment of pulp and paper industry effluent in lab scale when compared to pilot scale.